FORMULATION AND EVALUATION OF PROBIOTIC AND PREBIOTIC LOADED PELLETS BY EXTRUSION AND SPHERONIZATION FOR IMPROVED STORAGE VIABILITY - KUMAR S., HEMANTH; GOWDA, D. V.; H. V., GANGADHARAPPA; JAIN, VIKAS; CATHERINE, ARCHER ANN (International Journal of Applied Pharmaceutics, 2022)
Objective: The present study aims to prepare stains-loaded enteric-coated pellets by extrusion and spheronization technique for acidic environment protection and improve the viability of the strains during storage. Methods: Lactobacillus casei and Lactobacillus plantarum strains are proven to have various therapeutic and prophylactic uses in human beings, but low stability during storage and transit to site of action has limited their action. Pellets were prepared by incorporating probiotic strains D1-D9 (L. casei) and E1-E9 (L. plantarum) by further enteric-coating the pellets, which were evaluated for particle size, loss on drying, friability, micromeritic properties, viability, disintegration, survivability in acidic and bile juices, and stability studies for 90 d respectively. Results: The method employed for preparing the pellets showed good % yields with a particle rage of 1400-850 µm. LoD values were in the range of 3.07±0.30% to 2.13±0.11%; all the prepared pellets showed good flow properties and friability in an acceptable range. SEM images revealed that enteric-coated pellets had smooth and uniformly surfaces. The viability results ranged from 8.78±0.31 to 8.53±0.15 log CFU/g and 8.47±0.15 to 8.85±0.22 log CFU/g for both L. casei and L. plantarum enteric coated pellets, respectively. The Disintegration time for the pellets was<15 min in all the formulations. The enteric-coated probiotic pellets provided adequate protection against the acidic environment. Studies of survivability in simulated gastrointestinal conditions demonstrated that formulations D7 and E7 showed higher viability among the formulations at the end of 3 h. The stability studies showed that the formulations with a higher concentration of Inulin and pectin combination proved better viability of L. casei and L. plantarum strains in the formulation during 90 d of stability study. Conclusion: This study suggested that using extrusion and spheronization techniques can be employed to prepare pellets with prebiotics (Inulin and Pectin) which can be utilized to formulate probiotic dosage forms with improved viability in physiological conditions and real-time storage conditions